Kesan kehadiran ion ferik dalam pemendakan hidroksida logam - Siti Rozaimah Sheikh Abdullah,; Hii , Hiong Wei; Saleha Atan, (2004)
This research aims to investigate the effects of ferric ions on hydroxide precipitation of copper; zinc, lead, chromium and nickel metals individually as well as in mixed metals. The treatment method used was chemical precipitation using calcium hydroxide as the precipitation agent in the existence of ferric ions as one of the pollutants. The experiment was initially performed with the preparation of synthetic wastewater stocks that were diluted according to the experimental requirements. pH values of the solution were then initially reduced to pH 2 using nitric acid. 50 mL aliquots of sample were obtained at each pH increment and filtered through 0.45 mm porous cellulose nitrate membranes. The procedure was then repeated by adding ferric chloride solutions as a polluting metal. The alkaline medium was found to be the most suitable for metal precipitation purposes since all the optimum pH for all five metals occurred at alkaline medium. The minimum solubility of individual hydroxide precipitation for Cu, Ni, Zn, Pb and Cr were 2.34-5.4 mgL-1, 0-10.78 mgL-1, 1.35- 16.51 mgL-1, 2.34-10.89 mgL-1 and 1.09-5.38 mgL-1 respectively. With the presence of 50 mgL-1 ferric ions, the minimum solubility for Cu, Ni, Zn, Pb and Cr decreased to 2.00-9.44 mgL-1 and 0-4.17 mgL-1 respectively. Hence, the presence of ferric ions was able to effectively increase the metal precipitation as the formation of ferric hydroxide acted as an intermediate kinetic during metal hydroxide precipitation process. The precipitation effect if the presence of ferric ions was more noticeable in mixed metal solutions